Strengthening Business Sustainability and Enhancing Bamboo Craft Production Efficiency in the Kraosan Social Enterprise of Ngadiharjo Village - Pram Suryanadi; Catur Sugiarto; Khresna Bayu Sangka; Lisa Charisa Batara; Mi’raj Akbar Pradianto; Revy Lidiya Oni Marlina; Astri Suryanti; Andreansyah Saputra; Anggerka Harum Oktaviana (Ali Institute of Research and Publication, 2026)
This community service program was implemented in Ngadiharjo Village, Borobudur, in collaboration with Kraosan, a social enterprise specializing in bamboo handicrafts. The enterprise faces several challenges, including inconsistent product quality, unstructured workflows, and limited production technology, which have hindered its capacity to meet increasing market demand. The program was carried out through five systematic stages: (1) socialization, (2) technical training, (3) management assistance, (4) implementation of appropriate technology, and (5) impact evaluation. The evaluation results indicate a 77.8% increase in partners’ understanding, with the average score rising from 41.54 (pre-test) to 73.84 (post-test). The implementation of bamboo splitting and shaving machines demonstrated a substantial improvement in production efficiency by significantly reducing processing time while ensuring more precise and consistent product dimensions compared to manual methods. Furthermore, management assistance and brand identity development enhanced Kraosan’s readiness to enter the premium market segment. Overall, this program contributes to improving production capacity, increasing household income potential, and strengthening the social enterprise model in supporting poverty alleviation efforts in Ngadiharjo Village.